2007
DOI: 10.1177/0003319706292012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Venous Insufficiency on Activities of Daily Living and Quality of Life: Correlation of Demographic Factors With Duplex Ultrasonography Findings

Abstract: The study evaluates to what extent symptoms of chronic venous insufficiency (CVI) and functional venous incompetence as investigated using color-coded duplex ultrasonography may interfere with activities of daily living (ADLs). This study comprises a cross-sectional survey conducted in urban areas surrounding 24 Italian cities. A spontaneous sample of 5,187 subjects (4,457 women [mean age, 54 years] and 730 men [mean age, 61 years]), selected by advertising on television and in newspapers, underwent a clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 7 publications
2
30
0
2
Order By: Relevance
“…CVI is common among women. [7][8][9][10]20 Similar to the literature, we found that sex was an independent predictor of CVI. Increased BMI is also another risk factor for the development of CVI.…”
Section: Discussionsupporting
confidence: 83%
“…CVI is common among women. [7][8][9][10]20 Similar to the literature, we found that sex was an independent predictor of CVI. Increased BMI is also another risk factor for the development of CVI.…”
Section: Discussionsupporting
confidence: 83%
“…29 It is debatable whether VCT is a good marker for valve function and whether a subtle decline with age is detectable by this technique. None of the participants in our study fulfilled the criteria for reflux and therefore primary venous insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Signs such as varicose veins, edema, trophic skin changes and ulcers and symptoms such as pain, cramps, itching, heavy legs, burning and throbbing are often associated with limitations in activities of daily living and functional performance, along with psychological changes and changes to the perception of the health condition 5,[7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%